2017
DOI: 10.1159/000479558
|View full text |Cite
|
Sign up to set email alerts
|

Dose Distributions and Treatment Margins in Ocular Brachytherapy with 106Ru Eye Plaques

Abstract: Brachytherapy with 106Ru eye plaques is the most common treatment modality for small to medium-sized uveal melanomas in Europe. So far, no standardized or widely accepted dose prescription protocol for the irradiation of intraocular tumors with 106Ru eye plaques has been defined. For 125I plaques, the minimum dose required for tumor control should be at least 85 Gy. Concerning 106Ru plaques, the dose prescriptions at the University Hospital of Essen foresees minimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 18 publications
1
24
0
3
Order By: Relevance
“…Prescription procedures for Ru-106 treatments remain controversial [20]. Some centres use an apical prescribed dose of 85 Gy [1,24], some use 100 Gy to the apex [2,13], while others use at least 130 Gy to the apex along with restricted tumour base doses of at least 700 Gy [27]. Eccentrically located plaques are also reported frequently in the literature, and studies have indicated that this strategy can spare healthy tissue in some cases [5].…”
Section: Discussionmentioning
confidence: 99%
“…Prescription procedures for Ru-106 treatments remain controversial [20]. Some centres use an apical prescribed dose of 85 Gy [1,24], some use 100 Gy to the apex [2,13], while others use at least 130 Gy to the apex along with restricted tumour base doses of at least 700 Gy [27]. Eccentrically located plaques are also reported frequently in the literature, and studies have indicated that this strategy can spare healthy tissue in some cases [5].…”
Section: Discussionmentioning
confidence: 99%
“…No obstante, dosis menores de 50 Gy se asocian con fallos significativos en el control local de la enfermedad. En los resultados del Collaborative Ocular Melanoma Study (COMS), en el que se han utilizado placas oculares de 125 I, se especificó una dosis mínima obligatoria de 85 Gy para aplicar a todo el volumen objetivo [9]. Se recomienda tratar el tumor con una tasa de dosis comprendida entre 0,60 y 1,05 Gy/h, es decir, con una aplicación del implante durante un periodo que varía entre tres y siete días.…”
Section: La International Commission On Radiation Units Andunclassified
“…Localización del tumor en diagrama de retina Ser vicio Geológico C olombiano secos se encargan de mediar los movimientos de aducción, abducción, elevación, descenso, rotación medial y rotación lateral del globo ocular [13], y, aunque son mínimos, no se pueden despreciar. Por esta razón, se debe agregar un margen de tratamiento de radioterapia adicional (o margen de seguridad) al CTV definido [9]. Cabe resaltar que en este tipo de técnica no se incluye el término de volumen objetivo de planeación (PTV, sigla de planning target volume), debido a que en este término se tienen en cuenta factores de incertidumbre relacionados con el margen de la enfermedad subclínica, como los movimientos involuntarios (respiración) y errores en el posicionamiento.…”
Section: Distribución De Dosisunclassified
“…Из органосохраняющих методов лечения брахитерапия (БТ) с использованием различных радиоизотопов на протяжении полувека продолжает занимать лидирующую позицию и заслуженно считается «золотым стандартом» в схеме ведения больных данного профиля [2]. Использование контактных радиоактивных офтальмоаппликаторов (ОА) позволяет локально облучить опухоль, сохранить больному глаз, остаточное зрение и сохранить качество жизни [3].…”
Section: Introductionunclassified